Performance of geotextile-reinforced bases for paved roads - Saghebfar, Milad (Kansas State University, 2014)
Geotextiles have been widely promoted for pavement structure over the past 30 years. However, there is a lack of well-instrumented, full-scale experiments to investigate the effect of geotextile reinforcement on the pavement design. In this study, full–scale accelerated tests were conducted on eight lanes of pavement test sections. Six out of these eight sections had granular bases reinforced with different types of woven geotextiles. The reinforced base sections and the control sections (with unreinforced base) were paved with Superpave hot-mix asphalt. Base and subgrade materials were the same for all sections while the test sections had different asphalt and base layer thicknesses. Each section was instrumented with two pressure cells on top of the subgrade, six strain gages on the geotextile body, six H-bar strain gages at the bottom of the asphalt layer, two thermocouples and one Time Domain Reflectometer (TDR) sensor. The sections were loaded to 250,000 to 500,000 repetitions of an 80-kN single axle load of the accelerated pavement testing machine. The mechanistic response of each section was monitored and analyzed at selected number of wheel passes. Results indicate that properly selected and designed geotextile-reinforced bases improve pavement performance in term of rutting and reduced pressure at the top of the subgrade. Finite element (FE) models were developed and verified using results from the full-scale accelerated pavement tests. The calibrated model was used to investigate the effects of geotextile properties on the pavement responses. FE analysis shows that benefits of reinforcement are more evident when stiffer geotextile is used.
Keywords: Geotextile-reinforced bases; Full–scale accelerated test; Finite element model; Geosynthetic; Engineering (0537)